2018
DOI: 10.1111/1758-2229.12641
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting P acquisition strategies of the bacterial communities associated with legume and grass in subtropical orchard soil

Abstract: Phosphorus (P) cycling is a fundamental process driven by microorganisms, and plants can regulate P cycling directly or via their influence on the soil microbial community. However, the differential P cycling patterns associated with legumes and grass are largely unknown. Therefore, we investigated the microbial community involved in P cycling in subtropical soil grown with stylo (Stylosanthes guianensis, legume) or bahiagrass (Paspalum notatum, grass) using metagenomic sequencing. P fractionation indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
6

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 66 publications
2
23
1
6
Order By: Relevance
“…Large differences in the abundances of Betaproteobacteria in the monocots (68.4%) and dicots (37.8%) obviously contributed to the significant Mantel correlation between the evolutionary distances of host plants and the assemblies of bacterial root microbiomes (Figure 1a). This finding is confirmed by previous studies that reported that Betaproteobacteria are enriched in monocot roots (Bulgarelli et al ., 2015; Niu et al ., 2017; Zhou et al ., 2018). However, a significant Mantel correlation was still observed within the dicots (Figure 1a), and five Betaproteobacteria OTUs exhibited significant Mantel correlations among the 18 dicot species (Figure 5 and Table S3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large differences in the abundances of Betaproteobacteria in the monocots (68.4%) and dicots (37.8%) obviously contributed to the significant Mantel correlation between the evolutionary distances of host plants and the assemblies of bacterial root microbiomes (Figure 1a). This finding is confirmed by previous studies that reported that Betaproteobacteria are enriched in monocot roots (Bulgarelli et al ., 2015; Niu et al ., 2017; Zhou et al ., 2018). However, a significant Mantel correlation was still observed within the dicots (Figure 1a), and five Betaproteobacteria OTUs exhibited significant Mantel correlations among the 18 dicot species (Figure 5 and Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…For example, increases in Betaproteobacteria abundance occurred concomitantly with decreases in Actinobacteria abundance. The two bacterial groups exhibit different habitat enrichment patterns in the soil (Bulgarelli et al ., 2015; Zhou et al ., 2018). The Betaproteobacteria can colonize dead lignocellulosic matrices, whereas the Actinobacteria exclusively inhabit metabolically active host cells (Bulgarelli et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, phosphatase activity was not always correlated with P deficiency [ 51 , 52 , 53 ], while alkaline phosphatase enzymes are deemed to be principally derived from soil microbes [ 18 , 54 , 55 , 56 ]. Therefore, a more accurate understanding of the mechanisms of P acquisition by legumes and grasses is a prerequisite for their use in intercropping systems or as potential green manures for the acquisition and recycling of P in soil–plant systems [ 14 , 30 , 57 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that Neorickettsia helminthoeca also experienced drastic changes in the population in runs D and E. N. helminthoeca and Candidatus Solibacter sp. have been reported to be able to solubilize inorganic phosphorus in grass-field soil [ 47 ], although the roles of these species in methanogenic microbial communities are unknown. These results were in accordance with the decrease of richness and evenness of the microbial community in run E. Even though the population levels were low except for C. chauvoei , there is a possibility that changes in population of species shown in Table 3 may become indices prior to overacidification in the methane production process.…”
Section: Resultsmentioning
confidence: 99%